Periapical Lesions and Their Relationship to Schneider’s Membrane in Cone-Beam Computed Tomography - Cayo Rojas, César Félix (2020)
Objective. To determine the relationship between the height of the periapical lesions adjacent to the maxillary sinus and the thickness of the Schneider membrane evaluated with cone-beam tomography. Materials and Methods. The universe was made up of 2432 tomography scans and a sample of 976, by systematic random sampling, and took into account those that presented any of the variables and/or both. For the relationship analysis, the sample was distributed according to sex, maxillary side, and age; it was formed between 18 and 86 years, in age groups of 18–36 years, 37–48 years, 49–59 years, and 60–86 years. The quantitative variables of the statistic descriptive analysis, hypothesis tests, and Spearman correlation were recorded. Results. A significantly low correlation (p < 0.010) was observed between the periapical lesions and the thickness of the Schneider membrane in women (rho = 0.38) and men (rho = 0.32); in the same way, a significantly low correlation was observed in the age groups of 18–36 years (rho = 0.27) and 37–48 years (rho = 0.28), while a significantly moderate correlation was observed in the age groups of 49–59 years (rho = 0.45) and 60–86 years (rho = 0.44), and with respect to the sides, a significantly low correlation (rho = 0.28) was obtained for the right side and a significantly moderate correlation (rho = 0.45) was obtained on the left side. Conclusion. We found that the height of the periapical lesions and the thickness of the Schneider membrane are significantly related according to age, sex, and maxillary side, this relationship being accentuated at an older age and on the left side.